Functional Involvement of Thrombospondin in Platelet Aggregation Induced by Low Versus High Concentrations of Thrombin - Kao, K J; Shaut, David M; Klein, Paul A (Thrombosis and Haemostasis, 1986)
Thrombospondin (TSP) is a major platelet secretory glycoprotein. Earlier studies of various investigators demonstrated that TSP is the endogenous platelet lectin and is responsible for the hemagglutinating activity expressed on formaldehyde-fixed thrombin-treated platelets. The direct effect of highly purified TSP on thrombin-induced platelet aggregation was studied. It was observed that aggregation of gel-filtered platelets induced by low concentrations of thrombin (≤0.05 U/ml) was progressively inhibited by increasing concentrations of exogenous TSP (≥60 μg/ml). However, inhibition of platelet aggregation by TSP was not observed when higher than 0.1 U/ml thrombin was used to activate platelets. To exclude the possibility that TSP inhibits platelet aggregation by affecting thrombin activation of platelets, three different approaches were utilized. First, by using a chromogenic substrate assay it was shown that TSP does not inhibit the proteolytic activity of thrombin. Second, thromboxane B2 synthesis by thrombin-stimulated platelets was not affected by exogenous TSP. Finally, electron microscopy of thrombin-induced platelet aggregates showed that platelets were activated by thrombin regardless of the presence or absence of exogenous TSP. The results indicate that high concentrations of exogenous TSP (≥60 μg/ml) directly interfere with interplatelet recognition among thrombin-activated platelets. This inhibitory effect of TSP can be neutralized by anti-TSP Fab. In addition, anti-TSP Fab directly inhibits platelet aggregation induced by a low (0.02 U/ml) but not by a high (0.1 U/ml) concentration of thrombin. In conclusion, our findings demonstrate that TSP is functionally important for platelet aggregation induced by low (≤0.05 U/ml) but not high (≥0.1 U/ml) concentrations of thrombin. High concentrations of exogenous TSP may univalently saturate all its platelet binding sites consequently interfering with TSP-crosslinking of thrombin-activated platelets.
Keywords: Thrombospondin; Thrombin-induced platelet aggregation